PTH-078 Forward Progress Or Financial Extravagance? Counting The Cost Of Nice Guidelines For Chronic Hepatitis B. (9th June 2014) - Hudson, B; Badham, H; Lim, TY; Morrison, H; McCune, CA; Portal, AJ; Collins, PL; Gordon, FH
Abstract : Introduction: An estimated 180, 000 people in the UK are chronically infected with hepatitis B (HBV). NICE guidelines published in 2013 advocate changes in the management of this patient group. Recommendation toward use of peginterferon alfa-2a (PEG-IFN) as first line therapy, a reduced threshold for treatment initiation, and the monitoring of chronically infected individuals with annual elastography hold particular resource implications. University Hospitals Bristol (UHB) serves a largely urban population of approximately 350, 000, encompassing large immigrant communities, including a Somali population of approximately 10, 000. UHB provides an elastography service to an additional 3 district hospitals. Through analysis of our existing HBV patient population the resource implications of adopting 2013 NICE guidelines, in contrast to 2012 EASL guidelines, are assessed. Methods: Local HBV databases were scrutinised to identify all HBV patients attending over a one year period from november 2012. Patients defaulting follow-up during this period were excluded. A cost of treatment analysis was undertaken by reassessing each patient's treatment eligibility according to 2013 NICE guidance. Additional monitoring and clinic follow up costs were also calculated. Results: 154 patients were identified, 93 of whom were receiving antiviral nucleos (t)ide analogue treatment (24 initiated). 2 had initiated PEG-IFN. 61 were under monitoring only. All 24 patients starting therapy met NICE criteria for PEG-IFN, the excess cost of which was £137, 003 over a 1 year period. The estimated additional number of treatment clinic visits for this group is 202 (assuming an extra 8.4 visits/patient initiated). This analysis does not include increased demand for liason psychiatry and virology services. There would be 109 extra elastography appointments required for this cohort alone, amounting to a further 28 clinics a year. 3 district general hospitals currently refer patients to UHB for elastography, and this analysis does not account for the inevitable increase in such referrals. Conclusion: Implementation of 2013 NICE guidelines for management of chronic HBV represent a significant challenge to NHS resources. In addition to increased drug expenditure, markedly increased clinic capacity and specialist nurse provision will be required in our centre to facilitate increased used of PEG-IFN and to provide sufficient transient elastography for our region. Additional demands on virology and liason psychiatry services are also likely. Practical suggestions for improving efficiency and capacity, such as 'one stop' fibroscan and follow up clinics, are discussed. Disclosure of Interest: None Declared.